An acute oral dose of caffeine does not alter glucose kinetics during prolonged dynamic exercise in trained endurance athletes - Roy, B. D.; Bosman, M. J.; Tarnopolsky, M. A. (European Journal of Applied Physiology, 2001)
This study investigated the possible influence of oral caffeine administration on endogenous glucose production and energy substrate metabolism during prolonged endurance exercise. Twelve trained endurance athletes [seven male, five female; peak oxygen consumption (VO2max) = 65.5 ml·kg-1·min-1] performed 60 min of cycle ergometry at 65% VO2max twice, once after oral caffeine administration (6 mg·kg-1) (CAF) and once following consumption of a placebo (PLA). CAF and PLA were administered in a randomized double-blind manner 75 min prior to exercise. Plasma glucose kinetics were determined with a primed-continuous infusion of [6,6-2H]glucose. No differences in oxygen consumption (VO2), and carbon dioxide production (VCO2) were observed between CAF and PLA, at rest or during exercise. Blood glucose concentrations were similar between the two conditions at rest and also during exercise. Exercise did lead to an increase in serum free fatty acid (FFA) concentrations for both conditions; however, no differences were observed between CAF and PLA. Both the plasma glucose rate of appearance (Ra) and disappearance (Rd) increased at the onset of exercise (P<0.05), but were not affected by CAF, as compared to PLA. CAF did lead to a higher plasma lactate concentration during exercise (P<0.05). It was concluded that an acute oral dose of caffeine does not influence plasma glucose kinetics or energy substrate oxidation during prolonged exercise in trained endurance athletes. However, CAF did lead to elevated plasma lactate concentrations. The exact mechanism of the increase in plasma lactate concentrations remains to be determined.